Evaluation of Biochemistry Learning Based on OBE and KKNI in The Face of The World Of Work in Society 5.0 - Wahyuni, Diah; Rochintaniawati, Diana; Riandi, R; Rusdianto, R (Journal of Tropical Chemistry Research and Education, 2025)
This field study research was conducted to analyze Biochemistry lectures from the perspective of the Indonesian National Qualifications Framework (KKNI) and Outcome-Based Education (OBE) based university curriculum. Data collection techniques were carried out through observation of learning implementation in Biochemistry courses, interviews with lecturers teaching Biochemistry courses, and analysis of semester lecture plan (RPS) documents. The participants involved in this study were three lecturers and 83 students of the undergraduate study program of ipa education in one of the universities in Jember Regency. The Biochemistry course is in the upper level compulsory course group with the study of science concepts. From the KKNI perspective, this course needs to increase the Bloom level in the CPMK provided to match the profile of science study program graduates. From an OBE perspective, this course has a contribution to graduate learning outcomes in Specific Skills and supports the profile of graduates as Science Teachers.